Clinical and Histopathologic observations in a cohort of Libyan patients with Oral Lichen Planus - S H Ingafou, Mohamed; M Elmurtadi, Ali (Libyan Journal of Dentistry, 2017)
This study describes the clinical and histological features in a cohort of 72 Libyans with a histologically confirmed oral lichen planus (OLP) seen in the academic department of Oral Medicine & Oral Pathology of dental faculty in Benghazi in the period between 1997 and 2015. The cases were followed up clinically from the time of first visit up to periods extending from 4-14 years. In addition, serial biopsies were taken (whenever it deemed necessary) for those patients diagnosed with epithelial dysplasia to monitor its behaviour within the lesion. All the epithelial dysplastic changes were found in erosive, atrophic and bullous form, and none was detected in the white keratotic types. Only One case had undergone malignant transformation after 14 years of the first presentation. Most of the cases responded invariably to management by topical corticosteroids, however, systemic corticosteroids were used for short periods in 5 cases, while benzydamine hydrochloride proven to be beneficial for the relief of mild to moderate pain that sometimes associates with OLP.